On-line voltage stability monitoring and control in smart grid - A survey - Sahu P.; Verma M.K. (My University, 2025)
Most of the work on voltage stability assessment of power systems has concentrated on offline studies. With advancement in Phasor Measurement Unit (PMU) technology, it is quite possible to assess voltage stability margin of real time systems in smart grid. This paper has addressed on different works going on in the area of voltage stability monitoring and control using PMU technology. The report in this paper has elaborated on different methodologies which have been proposed in literature for optimal placement of PMUs for control of voltage stability margin in smart grid. The paper sets new scope for promising researchers for the best utilization of PMUs in online voltage stability monitoring and control in smart grid architecture. © 2015 IEEE.